Antibacterial effect of turmeric (curcuma ionga) extract : basis for an information guide - Jha, Pawan Kumar (Pangasinan : [s.n.], 2012)
This study dealt with the determination of the antibacterial activity of Turmeric (Curcuma longa) extract. Specifically it sought to answer the following problems: What are the active constituents present in Turmeric (Curcuma longa) extract based on the phytochemical screening? What is the antibacterial activity of the Turmeric (Curcuma longa) extract and the positive control used based on the zone of growth inhibition produced on the following bacteria: a. Gram positive bacteria. Staphylococcus pneumoniae, Staphylococcus aureus b. Gram negative bacteria, Escherichia coll Salmonella typh? Is there significant differences in the antibacterial activity as to the zone of inhibition among the different concentrations of Turmeric (Curcuma longa) extract and positive control in the following bacteria: a. Gram positive bacteria, Staphylococcus pneumoniae, Staphylococcus aureus b. Gram negative bacteria, Escherichiacoli, Salmonellatyph? What is the effect of the turmeric extract on the infected wound of Guinea pigs? What information material can be proposed to increase the awareness on the effect of Turmeric (Curcuma longa) extract? Moreover, the study utilized both experimental and descriptive method of research to implement the ideas and facts regarding this research: Antibacterial activities of the extract was determined using antibacterial susceptibility testing and in-vivo antibacterial activity utilizing guinea pigs with infected wounds as test animals. Staphylococcus aureus, Streptococcus pneumonia, Escherichia coli and Salmonella typhi were used as test bacteria. Data gathering was done through the reaction of the different bacteria to the various concentration of turmeric (Curcuma longa) extract using microbial inhibition test with the Mueller Hinton agar as the culture medium. The effect of turmeric (Curcuma longa) extract was seen through formation of zone of inhibition. The wider the zone of inhibition, the better the effect of the turmeric (Curcuma longa) extract against said specific bacterium. The study is delimited only on the identification of the different active constituents and the comparative analysis on the antibacterial activities of the turmeric (Curcuma longa) extract with regards to its different concentrations. The study did not take into account the isolation of the active constituents nor determine the specific active constituent present in turmenc (Curcuma longa) extract. The specific mechanism of action was not ascertained. This study was conducted at the VMUF- College of Pharmacy and the Department of Science and Technology - Cordillera, La Trinidad, Benguet Date gathered were tabulated and analyzed using statistical treatment. and the following statistical tool were used in the treatment of data and data analysis: Analysis of Variance (ANOVA) was used to determine the significant difference in the antibacterial activity as to the zone of inhibition among the different concentrations and positive control in Gram Positive and Gram Negative bacteria. All statistical calculations were based on 99 % confidence level.
Bibliography: pages 144-151.
CHED-La Union
Keywords: Bacteria -- Microorganisms